Структуризація та аналіз даних у зростаючих пірамідальних мережах - Gladun, V. P.; Vashchenko, N. D.; Velichko, V. Yu.; Tkachenko, Yu. G. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The paper deals with memory organization for intelligent systems in the form of growing pyramidal networks (GPS), which provides processes of concept formation, hierarchical regulation and classification of input information. The algorithm of GPS building is described for the case when object descriptions are introduced by parts. Results of GPS application in chemistry and material science are discussed.